Survival Outcome in Men with Prostate Cancer in Yazd Province, Central Iran, from 2001 to 2012 - Vahedian Ardakani, Hassan Ali; Moghimi, Mansour; Shayestehpour, Mohammad; Doosti, Masoud; Salari Shahrbabaki, Fahimeh (Asian Pacific Journal of Cancer Biology, 2017)
Background: Prostate cancer is the second-leading cause of cancer death among men in the world. This cancer has increased significantly during recent years in Iran and is the sixth most common malignancy in Iranian men. Survival rates for prostate cancer in Iran are unknown. The present study aimed to estimate survival of patients suffering from prostate cancer in Yazd, Iran. Methods: In this retrospective cohort study, data were collected from 100 men with prostate cancer registered in Shohadaye Kargar and Shahid Sadoughy hospitals in Yazd during the period 2001-2012. The Kaplan-Meier method was used to estimate the survival over time and Cox regression analysis was performed to calculate the hazard ratios according to demographic and risk variables. Results: The mean age of all patients was 74.4 years. They had a mean survival time of 70.78±4.94 month. The 1-year, 3-year, and 5-year survival rates were 97%, 73%, and 54%, respectively. A statistically significant correlation was found between age, tumor grade, cancer stage, treatment and survival time of patients (p<0.05). The worst survival was in men with Gleason score 8-10 and stage IV of prostate cancer. Data showed no significant association between place of residence and patients’ survival (p>0.05). Conclusion: In this study, 5-year survival of patients with prostate cancer was poor. Screening of men for cancer diagnosis in early stages and use of advanced treatment option, it seems to improve survival outcome. Further studies are needed to monitor the survival of patients with prostate cancer in Iran.